18 Digital Imaging and Other Ancillary Tools for Hair Transplantation Evaluation (Hair Transplantation, 2023)
In evaluating a person for a hair transplant, it is very important to take specific measurements of follicular unit density in the donor area. There are different tools to document and quantify hair density and plan the procedure such as the following: hair densitometer, videomicroscopy, Folliscope, Follysis, HairCheck, FotoFinder with TrichoScan and TrichoScale, and the ARTAS Hair Studio. Using technological advancements in digital imaging for hair loss can help in determining appropriate candidacy for hair restoration surgery and also guide the surgeon to achieve more consistent results.
Keywords: hair density; hair miniaturization; trichogram; photo documentation; patient consultation; hair transplant tools